Isolation of Flavonoids from Deguelia duckeana and Their Effect on Cellular Viability, AMPK, eEF2, eIF2 and eIF4E - Cursino, Lorena M. C. (2016)
Preparations of Deguelia duckeana, known in Brazil as timbó, are used by indigenous people to kill fish. Reinvestigation of its extracts resulted in the isolation and identification of 11 known flavonoids identified as 3,5,4’-trimethoxy-4-prenylstilbene (1), 4-methoxyderricidine (2), lonchocarpine (3), 4-hydroxylonchocarpine (4), 4-methoxylonchocarpine (5), 5-hydroxy-4’,7-dimethoxy-6-prenylflavanone (6), 4’-hydroxyisolonchocarpine (7), 4’-methoxyisolonchocarpine (8), 3’,4’,7-trimethoxyflavone (9), 3’,4’-methylenedioxy-7-methoxyflavone (10), and 2,2-dimethyl-chromone-5,4’-hydroxy-5’-methoxyflavone (11). Except for 1, 3, and 4 all of these flavonoids have been described for the first time in D. duckeana and the flavanone 6 for the first time in nature. Compounds 2, 3, 4, 7, 9, and 10 were studied for their potential to induce cell death in neuronal SK-N-SH cells. Only the chalcone 4 and the flavanone 7 significantly induced lactate dehydrogenase (LDH) release, which was accompanied by activation of caspase-3 and impairment of energy homeostasis in the MTT assay and may explain the killing effect on fish. Interestingly, the flavone 10 reduced cell metabolism in the MTT assay without inducing cytotoxicity in the LDH assay. Furthermore, the flavonoids 2, 3, 4, 7, and 10 induced phosphorylation of the AMP-activated protein kinase (AMPK) and the eukaryotic elongation factor 2 (eEF2). The initiation factor eIF4E was dephosphorylated in the presence of these compounds. The initiation factor eIF2alpha was not affected. Further studies are needed to elucidate the importance of the observed effects on protein synthesis and potential therapeutic perspectives.